Text mining: concept, process, and applications (Revista Brasileira de Contabilidade e Gestão, 2023)
Text mining is an extension of data mining, and can be defined as a process of extracting unknown and useful information from textual documents written in natural language. Since most information is stored in text form, text mining has high commercial value and can be applied in areas such as medicine and customer service.
Keywords: data mining; text mining; social networks